2006
DOI: 10.17221/3349-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium foliar application on its content in winter wheat grain

Abstract: The effect of foliar application of graduated Se rates (0.5, 1.0, 10 and 20 g Se/ha) on the winter wheat grain yield and Se accumulation in grain was investigated in the accurate field fertilization experiment. Selenium fertilization was realized together with the application of liquid fertilizer DAM-390 (30 kg N/ha) in the growth stage of the 6 th leaf (Zadoks = 29). Applied treatments of Se fertilization did not influence the yields of grain. These yields fluctuated within the range of from 5.98 to 6.08, 5.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
16
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 10 publications
5
16
1
Order By: Relevance
“…This result was in line with the general recommendation (application at GS-39 stage, at stem elongation) given for humid regions in temperate climates, such as those in central and northern Europe. In a similar study carried out on winter wheat (Ducsay & Ložek, 2006), when Se fertilizer was applied at the GS-29 stage at a dose of 10 g ha -1 , the Se concentration in the grain was much lower than that obtained in the present study. Although several other parameters could have affected such lower Se concentration in the grain, a very early application does not seem to be the most convenient.…”
Section: Total Se In the Grain And In The Flourcontrasting
confidence: 88%
See 1 more Smart Citation
“…This result was in line with the general recommendation (application at GS-39 stage, at stem elongation) given for humid regions in temperate climates, such as those in central and northern Europe. In a similar study carried out on winter wheat (Ducsay & Ložek, 2006), when Se fertilizer was applied at the GS-29 stage at a dose of 10 g ha -1 , the Se concentration in the grain was much lower than that obtained in the present study. Although several other parameters could have affected such lower Se concentration in the grain, a very early application does not seem to be the most convenient.…”
Section: Total Se In the Grain And In The Flourcontrasting
confidence: 88%
“…Although in 2010-2011 the precipitation was higher than in 2011-2012, the severe and prolonged drought occurring during 2010-2011 at full flowering might be the cause of the lower grain production and higher protein content, probably due to a dilution effect. Grain yield was not affected by the Se application timing, in clear agreement with Ducsay and Ložek (2006). In contrast, Chu et al (2013) found that, when Se was applied at joining-heading and Vol.…”
Section: Effects Of Treatments On Grain Yield and Grain Protein Contentsupporting
confidence: 69%
“…If 1 g of Se/ha as selenite was applied, 9.3% of this amount was transited to wheat grain. This transition represented 2.4% and 2.9% of total applied Se when the doses of 10 and 20 g Se/ha, were applied, respectively (Ducsay and Ložek 2006).…”
Section: Resultsmentioning
confidence: 96%
“…Selenium enrichment of fertilizers is intended for fertilizing of agricultural crops (agronomic biofortification) and plant breeding (or genetic biofortification); they are supposed to be the most effective ways to increase selenium intake by population, whereby selenium reaches the different levels of food chain (Lyons et al 2004, Hartikainen 2005, Ducsay and Ložek 2006. The way of biofortification and the form of selenium intended for this way remain open.…”
mentioning
confidence: 99%